Percutaneous assist devices in acute myocardial infarction with cardiogenic shock: Review, meta-analysis - Romeo, Francesco (World J Cardiol, 2016)
AIM: To assess the impact of percutaneous cardiac support in cardiogenic shock (CS) complicating acute myocardial infarction (AMI), treated with percutaneous coronary intervention. METHODS: We selected all of the studies published from January 1(st), 1997 to May 15(st), 2015 that compared the following percutaneous mechanical support in patients with CS due to AMI undergoing myocardial revascularization: (1) intra-aortic balloon pump (IABP) vs Medical therapy; (2) percutaneous left ventricular assist devices (PLVADs) vs IABP; (3) complete extracorporeal life support with extracorporeal membrane oxygenation (ECMO) plus IABP vs IABP alone; and (4) ECMO plus IABP vs ECMO alone, in patients with AMI and CS undergoing myocardial revascularization. We evaluated the impact of the support devices on primary and secondary endpoints. Primary endpoint was the inhospital mortality due to any cause during the same hospital stay and secondary endpoint late mortality at 6-12 mo of follow-up. RESULTS: One thousand two hundred and seventy-two studies met the initial screening criteria. After detailed review, only 30 were selected. There were 6 eligible randomized controlled trials and 24 eligible observational studies totaling 15799 patients. We found that the inhospital mortality was: (1) significantly higher with IABP support vs medical therapy (RR = +15%, P = 0.0002); (2) was higher, although not significantly, with PLVADs compared to IABP (RR = +14%, P = 0.21); and (3) significantly lower in patients treated with ECMO plus IABP vs IABP (RR = -44%, P = 0.0008) or ECMO (RR = -20%, P = 0.006) alone. In addition, Trial Sequential Analysis showed that in the comparison of IABP vs medical therapy, the sample size was adequate to demonstrate a significant increase in risk due to IABP. CONCLUSION: Inhospital mortality was significantly higher with IABP vs medical therapy. PLVADs did not reduce early mortality. ECMO plus IABP significantly reduced inhospital mortality compared to IABP.